A new architecture for ATM cell routing based on Banyan network - Ruggiero, Carlos Antônio; Colombini, Angelo Cesar (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance Computing, 2000)
Routing in ATM switches is very complex. The complexity increases when the applications require multicast capabilities. Both unicast and multicast traffic and also the Banyan network have only N² crossing points. Because of that, there is an inevitable contention for the same output link and a bottleneck point. It is important to mention that cost and speed of operation are essential requirements in ATM. The easy solution to this problem would be the buffer strategy. However, a better option is to modify the Banyan network in such a way that could keep its characteristics of auto routing, allowing a disassociation of Unicast and Multicast cell traffic inside the routing structure.